The impact of motor symptoms on self-reported anxiety in Parkinson's disease. (May 2017) - Salazar, Robert D.; Le, Asher M.; Neargarder, Sandy; Cronin-Golomb, Alice
Abstract: Objective: Anxiety is commonly endorsed in Parkinson's disease (PD) and significantly affects quality of life. The Beck Anxiety Inventory (BAI) is often used but contains items that overlap with common PD motor symptoms (e.g., "hands trembling"). Because of these overlapping items, we hypothesized that PD motor symptoms would significantly affect BAI scores. Methods: One hundred non-demented individuals with PD and 74 healthy control participants completed the BAI. PD motor symptoms were assessed by the Unified Parkinson's Disease Rating Scale (UPDRS). Factor analysis of the BAI assessed for a PD motor factor, and further analyses assessed how this factor affected BAI scores. Results: BAI scores were significantly higher for PD than NC. A five-item PD motor factor correlated with UPDRS observer-rated motor severity and mediated the PD-control difference on BAI total scores. An interaction occurred, whereby removal of the PD motor factor resulted in a significant reduction in BAI scores for PD relative to NC. The correlation between the BAI and UPDRS significantly declined when controlling for the PD motor factor. Conclusions: The results indicate that commonly endorsed BAI items may reflect motor symptoms such as tremor instead of, or in addition to, genuine mood symptoms. These findings highlight the importance of considering motor symptoms in the assessment of anxiety in PD and point to the need for selecting anxiety measures that are less subject to contamination by the motor effects of movement disorders. Highlights: The Beck Anxiety Inventory (BAI) assesses Parkinson's disease (PD) motor symptoms. Hallmark PD motor symptoms loaded onto one factor, and affected BAI scores. BAI scores significantly declined when PD motor items were removed. Motor items mediated the BAI difference between PD and normal control participants. PD anxiety assessments should distinguish between motor and mood symptoms.